Vias efetoras pelas quais a Hsp70 de Mycobacterium tuberculosis inibe a rejeição aguda em um modelo de aloenxerto cutâneo - Borges, Thiago de Jesus (2012)
Transplantation of solid organs has emerged as a viable therapeutic modality for the treatment of a variety of disorders. Rejection of solid organ allografts is the result of a complex range of interactions involving coordination between both the innate and adaptive immune system. Therewith, a major goal of clinical organ transplantation is to induce a donor-specific unresponsive state in a mature immune system that is free from long-term immunosuppression and chronic rejection. The limitations in the establishment of immunossupressive stratagies led us to search new methods to the modulation of the homeostatic mechanisms that limit and prevent inflammatory responses in allograft tissue. The heat shock protein 70 (Hsp70) has a protective and antiinflamatory role in several animals models like arthritis, colitis, pulmonary fibrosis and brain injury. This protein can modulates both the innate and adaptative immune system. Our group demonstrated that Mycobacterium tuberculosis Hsp70 (Mt Hsp70) can inhibit bone marrow dendritic cells (BMDCs) maturation; however the mechanisms involved in this process has not been completely elucidated. In the present work, we demonstrated that Mt Hsp70 inhibited the acute rejection in two allograft models (a tumor model and a skin allograft model).In both models, we observed an involvement of Tregs. In addition, s.c. Mt Hsp70 injection leds to an increase in Treg population and IL-10 production in the draining lymph node. We also observed that the inhibition of acute rejection induced by Mt Hsp70 was dependent on the presence of toll-like receptor (TLR) 2 in the allograft, and not in the host. In BMDCs, we demonstrated that IL-10 production induced by Mt Hsp70 is dependent on TLR2. Also, we analyzed the phosphorylation of ERK, p38 and Akt after Mt Hsp70 stimulus. We observed an increase in p-ERK expression, but no difference in p-38 and p-Akt levels. The inhibition of ERK abolished the IL-10 production induced by Mt Hsp70. We propose that Mt Hsp70 effect on DCs can be used as a therapeutic approach in transplantation models.